JUSTIFICATION THE PERSPECTIVE SYSTEM OF MONETARY ALLOWANCE OF THE MILITARY PERSONNEL OF THE ARMED FORCES OF UKRAINE BASED ON THE EXPERIENCE OF NATO COUNTRIES - Chimyshenko, Serhii; Tsiukalo, Liudmyla; Bachinskyi, Yevhen (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . The armed aggression of the russian federation against Ukraine has led to a significant increase in the number of the Ukrainian Defense Forces. Typically, during the war, it is important to ensure an adequate level of monetary allowance for military personnel involved in the defense of Ukraine's state sovereignty. Before that, starting from February 1, 2022, the system of remuneration of the Armed Forces of Ukraine underwent significant changes. However, today, the national system mainly consists of salaries by military ranks, official salaries and additional types of salaries. At the same time, very often the number and share of additional types of salaries prevails in the composition of monetary allowance, which contradicts of its principles – transparency of its calculation. Therefore, given the current military, political and economic conditions, it is important to study the current system of monetary support of the AFU military personnel and to identify areas for its improvement in accordance with NATO standards. The purpose of the article is to conduct a study on the development of a perspective model of monetary allowance for the military personnel of the Armed Forces of Ukraine based on the experience of NATO countries.M e t h o d s . The methodology of the study is based on the use of general scientific methods, in particular: analysis and synthesis; the method of analogy is used for the proposed model of a perspective system of monetary allowance of the military personnel of the Armed Forces of Ukraine based on the experience of NATO countries.R e s u l t s . The main directions of improvement of the current system of monetary allowance for military personnel of the Armed Forces of Ukraine, based on military rank and years of service are substantiated.C o n c l u s i o n s . The article proposes and substantiates the development of a perspective model of monetary allowance of the military personnel of the Armed Forces of Ukraine based on the experience of NATO countries.
Keywords: monetary allowance of the military personnel, basic salary, perspective model, NATO countries